Spatiotemporal and kinetic characteristics during maximal sprint running in fast running soccer players - Yohei Takai; Terumitsu Miyazaki; Norihide Sugisaki; Takaya Yoshimoto; Naotoshi Mitsukawa; Kai Kobayashi; Hiroyasu Tsuchie; Hiroaki Kanehisa (PLoS ONE, 2025)
This study aimed to elucidate spatiotemporal and kinetic variables in fast-running soccer players in comparison with sprinters or slow-running soccer players. Sixty-seven male soccer players and 17 male sprinters (Sp) performed 60-m maximal effort sprint running. The soccer players were classified into three groups: high-speed (SOCHigh), medium-speed, and low-speed (SOCLow). The antero-posterior and vertical ground reaction forces were measured with a 50-m long force plates system at every step during the sprint. Step length and step frequency were also computed from the position of center of pressure, contact time, and flight time. During the initial acceleration phase, SOCHigh exhibited similar running speeds to Sp. This was attributed to a higher step frequency in SOCHigh compared to Sp, while net antero-posterior impulse was lower in the former than in the later. In the range of running speed from 7.5 m/s to 8.5 m/s, net antero-posterior impulse for SOCHigh was similar to that for Sp. At 9.0 m/s, SOCHigh exhibited a lower net antero-posterior impulse compared to Sp, primarily due to a reduced propulsive impulse. Additionally, vertical impulse during the braking phase was larger in SOCHigh compared to Sp, due to a longer braking time, while vertical impulse during the propulsive phase was smaller, due to a tendency for a reduced propulsive time and vertical force during the corresponding phase. Compared to SOCLow, SOCHigh exhibited higher step frequency through sprint running and longer step lengths from the 2nd acceleration phase to maximal speed phase. Additionally, net antero-posterior impulse at the same running speed was greater in SOCHigh compared to SOCLow. Vertical impulse was lower during the braking phase but higher during the propulsive phase in SOCHigh than in SOCLow. Thus, the sprint mechanics of SOCHigh is characterized by a similar ability of speed acquisition up to the 2nd acceleration as sprinters. However, at 9.0 m/s or over, SOCHigh exhibits a greater vertical impulse, leading to a lower step frequency.